Suriname : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper describes the revenue instability and its consequences for Suriname. It explores some options for policy rules that could be considered in the case of Suriname. The paper analyzes inflation in Suriname from its historical and international perspectives, reviews the monetary policy instruments and the institutional framework, and describes the exchange rate regime and its main developments. The paper also analyzes the type of macroeconomic shocks and the domestic transmission mechanism for Suriname.